Cafe-au-lait spots with resistant hypertension are an indicator of pheochromocytoma: a rare case report - Amri, Meriam (2024)
This case report is one of the rare cases of bilateral pheochromocytoma associated with neurofibromatosis type 1. The interest lies in the clinical form in which the diagnosis was revealed. We report the case of a 38-year-old woman admitted for severe hypertension resistant to triple therapy. Clinical examination revealed Cafe-au-lait spots, which are pigmented birthmarks that appear as patches on the skin with a light to dark brown colour. More than six spots are present in an estimated 95% of people diagnosed with neurofibromatosis type 1 (NF1). Abdominal computed tomography (CT) showed bilateral adrenal tumor involvement. The diagnosis of pheochromocytoma was made by measuring urinary Vanillylmandelic acid (VMA). The evolution was favorable after the excision of the tumor, with normalization of blood pressure. In conclusion: resistant hypertension with café au lait spots may indicate pheochromocytoma, especially bilateral, suggesting an underlying genetic condition like NF1, warranting systematic screening.